Pattern of Respiratory Morbidity in the Catering Population of Rural Health and Training Centre, Bhopal, Madhya Pradesh - Sanjay Kumar Gupta; Neeraj Khare; Samarth Sharma (Medsci Publications, 2017)
Introduction: Respiratory tract infections are perhaps the most common human ailment. It is estimated that Bangladesh, India, Indonesia and Nepal together account for 40 per cent of the global ARI mortality. The research was done to study the trend and pattern of respiratory diseases and demographic characteristics. Methodology: A hospital based retrospective study was carried out at rural health and training centre from 2006-2011. Observations: The trend of respiratory morbidity in rural health and training centre catering area was increasing from 2006-2011(2.79-14%), than little dip thereafter. Maximum percentage of respiratory patients were reported in 2012 (23.78%) followed by in 2009(19.96%). Trend of respiratory problems among 0-5 years of age from 2006-2009 in increasing trend (3.3% -13.26%) thereafter slight decrease in percentage observed. Out of all respiratory problems most common was upper respiratory tract infection (78.30%) followed by ARI/Pneumonia (15.92%). Over all contribution of respiratory morbidity among patients attending rural health and training centre was 17.09%. Conclusion: Respiratory diseases trend at rural areas were in increasing trend and most of the cases occurred of upper respiratory tract infection.